Cu2SnS3 based solar cell with 3% efficiency. Issue 1 (29th October 2015) - Chierchia, R.; Pigna, F.; Valentini, M.; Malerba, C.; Salza, E.; Mangiapane, P.; Polichetti, T.; Mittiga, A.
Abstract: Cu2 SnS3 is an earth abundant material suitable for photovoltaic applications. Unfortunately, the material still suffers of a low diffusion length of the carriers due to the presence of spurious phases, voids, defects and small grain size. In order to improve the quality of our samples, the influence of the deposition parameters on its structural properties has been studied. The solar cell obtained with the optimized Cu2 SnS3 has shown an external quantum yield larger than 80% around 500 nm a conversion efficiency in the order of 3%, a Jsc of 26 mA and a Voc of 240 mV, one of the world best result obtained with a Cu2 SnS3 based solar cell. Furthermore the external quantum yield at wavelength larger than 1200 nm is still around 30% making this material interesting for IR detectors also. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)